2022
DOI: 10.1038/s41467-022-28147-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the efficiency of oxygen-evolving electrolysis on the Moon and Mars

Abstract: Establishing a permanent human presence on the Moon or Mars requires a secure supply of oxygen for life support and refueling. The electrolysis of water has attracted significant attention in this regard as water-ice may exist on both the Moon and Mars. However, to date there has been no study examining how the lower gravitational fields on the Moon and Mars might affect gas-evolving electrolysis when compared to terrestrial conditions. Herein we provide experimental data on the effects of gravitational fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…With the advantages of long life span, low cost, large capacity, earth-abundant elctrocatalysts and mature system integration, AWEs are more suitable for the large-scale industrial hydrogen production among these three technologies [22][23][24] , especially for the promising direct seawater electrolysis [25][26] . The microcosmic electrochemical principles about AWEs are well studied based on the small-scale electrolysers (usually tens of milliwatts ~ hundreds of watts), like OER and anode materials, HER and cathode materials, membrane, mass transfer, gas-liquid two phase flow and so on [27][28][29][30][31][32][33] . Usually, the established models and analysis methods are based on the lumped parameters, and the related phenomena of small-scale electrolysers can be accurately predicted through these microcosmic electrochemical principles.…”
Section: Current Bunching Effect Of Large-scale Alkaline Hydrogen Evo...mentioning
confidence: 99%
“…With the advantages of long life span, low cost, large capacity, earth-abundant elctrocatalysts and mature system integration, AWEs are more suitable for the large-scale industrial hydrogen production among these three technologies [22][23][24] , especially for the promising direct seawater electrolysis [25][26] . The microcosmic electrochemical principles about AWEs are well studied based on the small-scale electrolysers (usually tens of milliwatts ~ hundreds of watts), like OER and anode materials, HER and cathode materials, membrane, mass transfer, gas-liquid two phase flow and so on [27][28][29][30][31][32][33] . Usually, the established models and analysis methods are based on the lumped parameters, and the related phenomena of small-scale electrolysers can be accurately predicted through these microcosmic electrochemical principles.…”
Section: Current Bunching Effect Of Large-scale Alkaline Hydrogen Evo...mentioning
confidence: 99%
“…Given the considerable technical challenges associated with conducting any detailed experimental study of bubble behavior in molten salts at high temperatures, let alone interrogating such systems under reduced gravity, it may be that studying aqueous solutions at near-ambient temperature could serve as a useful and more accessible proxy for FFC-Cambridge electrolysis at high temperatures. With this in mind, Lomax et al (2022) recently investigated the influence of gravity on the oxygen evolution reaction during electrochemical water-splitting at ambient temperature across the gravitational range 10 −2 – 8 g using electrolysis cells mounted on a centrifuge 86 . By operating the system during parabolic flights, g levels below 1 could be obtained.…”
Section: Outlook: Open Research Questions Experiments Suggestions And...mentioning
confidence: 99%
“…In practice, electrochemical devices evolve multiple bubbles on the electrodes 60,86,87 , which interact in a complex, nonlinear manner, reaching a so-called 'self-organized state'. Selforganization depends strongly on convection 88 , which evidently depends on buoyancy or lack thereof.…”
Section: Computational Modelling Perspectives On Gas Bubble Growth An...mentioning
confidence: 99%
“…High-temperature, solid-oxide electrolysis (SOEC) systems, which have recently matured with significant gains in reliability and performance (5), have the potential to achieve lower specific energy levels than incumbent technologies such as alkaline electrolysis cell (AEC) and proton electrolyte membrane (PEM) electrolyzers (6). In addition, it has been shown that the efficiency of PEM and other electrolyzers that operate on liquid water is decreased under lunar gravity due to the decreased rate of buoyancy driven gas phase separation in reduced gravity conditions (7). SOECs based on doped-zirconia electrolytes, operate at temperatures > 700C and electrolyze steam rather than liquid water.…”
Section: Introductionmentioning
confidence: 99%